Mechanism of ERK/CREB pathway in pain and analgesia - Zhen, Weizhe; Zhen, Hongjun; Wang, Yuye; Chen, Leian; Niu, Xiaoqian; Zhang, Bin; Yang, Ziyuan; Peng, Dantao (Frontiers in Molecular Neuroscience, 2023)
Research has long centered on the pathophysiology of pain. The Transient Receiver Potential (TRP) protein family is well known for its function in the pathophysiology of pain, and extensive study has been done in this area. One of the significant mechanisms of pain etiology and analgesia that lacks a systematic synthesis and review is the ERK/CREB (Extracellular Signal-Regulated Kinase/CAMP Response Element Binding Protein) pathway. The ERK/CREB pathway-targeting analgesics may also cause a variety of adverse effects that call for specialized medical care. In this review, we systematically compiled the mechanism of the ERK/CREB pathway in the process of pain and analgesia, as well as the potential adverse effects on the nervous system brought on by the inhibition of the ERK/CREB pathway in analgesic drugs, and we suggested the corresponding solutions.